Digital Research and Education in Architectural Heritage : 5th Conference, DECH 2017, and First Workshop, UHDL 2017, Dresden, Germany, March 30-31, 2017, Revised Selected Papers /: 5th Conference, DECH 2017, and First Workshop, UHDL 2017, Dresden, Germany, March 30-31, 2017, Revised Selected Papers. (2018) - Unknown
No abstract available